Pengaruh Realisasi Pajak Kendaraan Bermotor (PKB) Dan Bea Balik Nama Kendaraan Bermotor (BBN-KB) Terhadap Pendapatan Asli Daerah Kabupaten Bangka - Sudarcun, Sudarcun; Fikri, Zakiyudin; Marlina, Marlina (Journal of Government Science Studies, 2023)
This study aims to determine the effect of the Realization of Motorized Vehicle Tax (PKB) and Motorized Vehicle Ownership Fee (BBN-KB) on Bangka Regency Regional Original Income. The research method used is quantitative research with an associative approach. The data used are primary data obtained from data on the realization of Motor Vehicle Taxes and Transfer Fees for Motorized Vehicles and the Realization of Local Own Revenue in Bangka Regency. The data analysis technique uses multiple regression with hypothesis testing using the t test and determination test. The results showed that the variable X1 (motor vehicle tax) obtained a significance value of 0.002, less than 0.05. it can be concluded that the variable X1 (Motor Vehicle Tax) has a positive and significant effect on Y (Local Original Income). Likewise, the X2 variable (Motor Vehicle Transfer Fee) obtains a significance value or Prob of 0.000 less than <0.05 (5%), the X2 variable (Motor Vehicle Transfer Fee) has a positive and significant effect on Y (Regional Original Income) ). Based on the results of the F test, it shows that the effect of X1 and X2 simultaneously on Y is 0.000, less than <0.05 and the calculated F value of 330,749 is greater than F table 5.75. this means that there is an effect of X1 and X2 simultaneously (simultaneously) on Y (Regional Own Revenue. The test results terminate in the R-squared value of 0.994 (99.4%) which means that the variables X1 (Motor Vehicle Tax) and X2 (motorized vehicle transfer fee) affect the Y variable (local original income) by 99.4%, the remaining 1.6% is influenced by other variables not included in the model.The conclusion is that the realization of motorized vehicle taxes and transfer of title fees has a significant effect on regional original income in Bangka Regency.